Pengaruh Kualitas Produk, Harga, Promosi Terhadap Loyalitas Pelanggan CV. Aneka Karya Bogor - Nurpadilah, Rifki; Samsuri, Samsuri; Yulianingsih, Yulianingsih (Jurnal Ilmiah Global Education, 2024)
This study aims to analyze and identify the effect of product quality, price and promotions both simultaneously and partially on customer loyalty CV. Aneka Karya Bogor. Questionnaires were distributed to 52 respondents who were taken by techniquenon probability sampling with a saturated sampling procedure or all members of the population are used as samples. The questionnaire was tested with validity test, reliability test and classical assumption test. The test results are valid, reliable, and can be used for regression data. The analytical method used in this research is descriptive and verification method. The results show that product quality, price and promotion variables both simultaneously and partially have a positive and significant effect on customer loyalty CV.Aneka Karya Bogor.